Slight excess at 130 GeV in search for a charged Higgs boson decaying to a charm quark and a bottom quark at the Large Hadron Collider. (1st August 2022) - Akeroyd, A G; Moretti, Stefano; Song, Muyuan
Abstract: Searches for a charged Higgs boson ( H ± ) decaying to a charm quark and a bottom quark ( H ± → cb ) have been carried out at the Large Hadron Collider (LHC) in the decay of top quarks ( t → H ± b ). In a recent search by the ATLAS collaboration (with all run II data, 139 fb −1 ) a local excess of around 3 σ has been observed, which is best fitted by a charged Higgs boson with a mass ( m H ± ) of around 130 GeV and a product of branching ratios (BRs) given by BR( t → H ± b ) × BR( H ± → cb ) = 0.16% ± 0.06%. In the context of two-Higgs-doublet models (2HDM) with independent Yukawa couplings for H ± we present the parameter space for which this excess (assuming it to be genuine) can be accommodated, taking into account the limits from LHC searches for H ± → cs and H ± → τν at m H ± = 130 GeV and the constraint from b → sγ . It is then shown that such an excess cannot be explained in 2HDMs with natural flavour conservation, but can be accommodated in the flipped three-Higgs-doublet model (3HDM) and in the aligned 2HDM (A2HDM). Upcoming searches with 139 fb −1 in the channels H ± → cb (CMS), H ± → cs (ATLAS/CMS) and H ± → τν (ATLAS/CMS) will determine if the excess is the first sign of an H ± with m H ± = 130 GeV.